Pengaruh Angin dan Curah Hujan Terhadap Hasil Tangkapan Ikan Layang yang Berbasis di PPS Kendari Sulawesi Tenggara - Dito Hermansyah; Muslim Tadjuddah; Abdullah Abdullah; Naslina Alimina; Ahmad Mustafa; Syamsul Kamri (Universitas Halu Oleo, 2023)
Southeast Sulawesi Province is one of the provinces with a sizeable amount of fish production, the Kendari Ocean Fishery Port (PPS) is one of the largest fishing ports in Indonesia which is located in Southeast Sulawesi. In carrying out fishing voyages, they pay great attention to weather conditions so they can get lots of fish and not face storms/bad weather when fishing. Based on this, this research was conducted with the aim of knowing: 1) the effect of wind speed on the catch of flying catfish 2) the effect of rainfall on the catch of flying catfish 3) the relationship between wind speed and rainfall on the catch of flying catfish. The research was conducted in September - October 2022 with data collection locations in two different places, namely Kendari Ocean Harbor Fishery and Kendari Class II Maritime Meteorological Station. Based on the results of this study indicate that the wind speed in the Banda Sea is comparable to the catch of flying fish. Meanwhile, rainfall in the Banda Sea is inversely proportional to the catch of flying catfish, where rainfall has no significant relationship with the volume of fish production obtained around the Banda Sea. From the analysis that has been done, it can be concluded that the wind speed in the Banda Sea is sufficient to prove the existence of a relationship to the activity of catching flying catfish. Meanwhile, rainfall in the Banda Sea is not enough to prove that there is an effect, especially on the activity of catching flying catfish. Suggestion from this research need to do further research by adding oceanographic factors.